Adsorption of Cu (II) and Cr (III) ions from aqueous medium in fixed bed column - Sabadash, Vira; Gumnitsky, Jaroslav (Національний університет "Львівська політехніка", 2018)
The adsorption of Copper (II) and Chromium (III) from aqueous solution by natural zeolite was investigated in fixed bed column. The effects of selected operating parameters such as flow rate and bed depth were evaluated. The breakthrough data are fitted well to Bed Depth Service Time (BDST) and Thomas models with high correlation coefficient, R2 = 0,91. The results showed that zeolite can be an effective adsorbent for Copper (II) and Chromium (III) removal.
Keywords: copper, heavy metals, adsorption, wastewater